Effect of Mixing Height on Box Model Calculation in Sulfur Dioxide Dispersion Modeling of Oil and Gas Industries - Reyhan Adista Ramadhani; Mohamad Mirwan; Okik Hendriyanto; Firra Rosariawari (Yayasan Literasi Sains Indonesia, 2023)
This study was conducted to determine the effect of height in the calculation of box model dispersion modeling. The experimental method was conducted using sample data of sulfur dioxide exhaust emissions produced by the oil and gas industry. The samples were obtained from an oil and gas company that produces sulfur dioxide emissions. There are two types of data obtained, namely hourly emission data and daily emission data generated by the industry with the amount of data obtained for 360 days. The results showed that the mixing height used in the box model formulation affects the results of the calculation. The optimal mixing height obtained from the study was 75 meters where all sample data used in the calculation showed that there were only 3.5% or 11 samples that did not meet the ambient air quality standards. The results also showed that the higher the mixing height used, the lower the emission of sulfur dioxide emission dispersion modeling calculation results. While calculations with lower mixing height will produce results that are inversely proportional to the concentration of sulfur dioxide emissions, the concentration of sulfur dioxide emissions produced will be higher. Therefore, sulfur dioxide dispersion modeling using a box model can be an alternative in determining the concentration of sulfur dioxide emissions produced.